Battling Underaged Online Video Gamers: Probing the Negative Effects of Online Video Gaming Addictions on Young Adolescents - John Demuyakor (Asian Journal of Media and Communication, 2021)
Many countries, including China, have declared online video gaming addictions among children and young adolescents as a public health emergency. With these growing concerns about the number of times children and young adolescents of school-going age spend time playing online video games, this study seeks to examine the adverse effects of online video gaming among young adolescents aged 13-17. This article drew on the theory of online gaming addiction and employed a qualitative research design through in-depth interviews. This study has collected data from 40 respondents in five public junior high schools in the Chaoyang District of Beijing, China. The data analysis was done through consolidated thematic analysis. This study finds that online video gaming platforms have significantly resulted in excessive addictions and negatively affected students' educational achievements, social relations, and physical and mental health.Â Keywords: online video games; addictions; young adolescents; Chinaâ€™s public junior high schools. Â